Hard Pitch Lake, La Brea, Trinidad B.W.I. - (:unkn) unknown (Waterman, the Hatter, Clothier and Outfitter, Trinidad, 2009)
Photo of Hard Pitch Lake at La Brea, Trinidad. Some persons visible are digging the hard pitch while others are observing. At centre is a cart with large wheels waiting to transport the slabs of pitch away.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Pitch--Trinidad and Tobago; Asphalt industry--Trinidad and Tobago; Working class--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--La Brea; Carriages and carts--Trinidad and Tobago; Pitch Lake, The (La Brea)